Comparison and gradation in Indo-European - Keydana, Götz; Hock, Wolfgang; Widmer, Paul; Ackermann, Katsiaryna; Dupraz, Emmanuel; Enger, Hans-Olav; Fellner, Hannes A.; Genesin, Monica; Griffith, Aaron; Höder, Steffen; Ittzés, Máté; Jäger, Agnes; et al. (The Mouton Handbooks of Indo-European Typology ;, 2021)
The ability to compare is fundamental to human cognition. Expressing various types of comparison is thus essential to any language. The present volume presents detailed grammatical descriptions of how comparison and gradation are expressed in ancient Indo-European languages. The detailed chapters devoted to the individual languages go far beyond standard handbook knowledge. Each chapter is structured the same way to facilitate cross-reference and (typological) comparison. The data are presented in a top-down fashion and in a format easily accessible to the linguistic community.The topics covered are similatives, equatives, comparatives, superlatives, elatives, and excessives. Each type of comparison is illustrated with glossed examples of all its attested grammatical realizations.The book is an indispensable tool for typologists, historical linguists, and students of the syntax and morphosyntax of comparison.